Interactions between the metabolic reprogramming of liver cancer and tumor microenvironment - Yang, Haoqiang; Li, Jinghui; Niu, Yiting; Zhou, Tao; Zhang, Pengyu; Liu, Yang; Li, Yanjun (Frontiers in Immunology, 2025)
Metabolic reprogramming is one of the major biological features of malignant tumors, playing a crucial role in the initiation and progression of cancer. The tumor microenvironment consists of various non-cancer cells, such as hepatic stellate cells, cancer-associated fibroblasts (CAFs), immune cells, as well as extracellular matrix and soluble substances. In liver cancer, metabolic reprogramming not only affects its own growth and survival but also interacts with other non-cancer cells by influencing the expression and release of metabolites and cytokines (such as lactate, PGE2, arginine). This interaction leads to acidification of the microenvironment and restricts the uptake of nutrients by other non-cancer cells, resulting in metabolic competition and symbiosis. At the same time, metabolic reprogramming in neighboring cells during proliferation and differentiation processes also impacts tumor immunity. This article provides a comprehensive overview of the metabolic crosstalk between liver cancer cells and their tumor microenvironment, deepening our understanding of relevant findings and pathways. This contributes to further understanding the regulation of cancer development and immune evasion mechanisms while providing assistance in advancing personalized therapies targeting metabolic pathways for anti-cancer treatment.